PENDAMPINGAN PERHITUNGAN HARGA POKOK PRODUKSI PADA USAHA MIKRO MAKANAN RINGAN DI DUSUN KWARASAN, NOGOTIRTO, GAMPING, SLEMAN - Hapsari, Yaning Tri; Marfuah, Hasti Hasanati; Kurniawanti, Kurniawanti; Samodro, Guntur; Dwinugroho, Theofilus Bayu (Jurnal Terapan Abdimas, 2023)
Abstract. Cost of Production (HPP) is an important element to assess the success (performance) of a trading or manufacturing company. Especially in determining the selling price and calculating the profit and loss of each product. Based on observations and interviews with “KREES” Banana Chips and Cheese Stick SME Owners, it is known that there are difficulties in recognizing what cost components must be calculated, thus causing difficulties in determining the optimal selling price to increase profits. The purpose of carrying out PKM activities is to provide assistance in calculating the Cost of Production (HPP) for UKM Banana Chips and Cheese Sticks "KREES".The method used in this dedication is in the form of face-to-face in delivering material, debriefing and discussing the calculation of the cost of production. The result of this mentoring and training is that partners understand enough about the material provided. So far, partners have indirectly carried out simple calculations in determining the cost of production so that the material provided is easily accepted. The impact of this service is an increase in partners' knowledge of the cost components for calculating the cost of production. Partners are helped by the report format for calculating the cost of production made by servants. This format assists partners in detailing the cost components used in calculating the cost of production. Another impact is that the financial records are more orderly and neat so as to increase the accuracy of calculating the cost of production. Abstrak. Harga Pokok Produksi (HPP) merupakan elemen penting untuk menilai keberhasilan (performance) dari perusahaan dagang maupun manufaktur. Terutama dalam penetuan harga jual dan menghitung laba rugi dari setiap produk. Berdasarkan pengamatan dan wawancara dengan Pemilik UKM Keripik Pisang dan Stick Keju “KREESS”, diketahui adanya kesulitan untuk mengenali komponen biaya apa saja yang harus dihitung, sehingga menyebabkan kesulitan dalam menentukan harga jual yang optimal untuk meningkatkan keuntungan. Tujuan dilakukannya kegiatan PKM adalah untuk memberikan pendampingan dalam menghitung Harga Pokok Produksi (HPP) pada UKM Keripik Pisang dan Stick Keju “KREESS”. Metode yang digunakan dalam pengabdian ini adalah dalam bentuk tatap muka dalam penyampaian materi, tanya jawab serta pembahasan perhitungan harga pokok produksi. Hasil dari pendampingan dan pelatihan ini yaitu mitra cukup paham akan materi yang diberikan. Selama ini mitra secara tidak langsung sudah melakukan perhitungan sederhana dalam menetapkan harga pokok produksi sehingga materi yang diberikan mudah diterima. Dampak pengabdian ini adalah peningkatan pengetahuan mitra tentang komponen biaya untuk perhitungan harga pokok produksi. Mitra terbantu dengan format laporan perhitungan harga pokok produksi yang dibuatkan oleh pengabdi. Format ini membantu mitra dalam merinci komponen biaya yang digunakan dalam perhitungan harga pokok produksi. Dampak lainnya yaitu pencatatan keuangan semakin teratur dan rapi sehingga meningkatkan akurasi HPP.